Optimizing Google Apps in Improving the Skills and Productivity of the Young Generation of Bojong Village Pondok Kelapa - Sofyan, Yan; Yudha, Afri; Syofian, Suzuki; Tri Mahardika, Bagus (Fakultas Teknik Universitas Darma Persada, 2024)
Effective and efficient administrative and office management remains a primary challenge for organizations in the digital era. This community service activity aims to enhance the understanding and skills of Bojong youth in utilizing Google applications (Google Drive, Google Docs, Google Sheets, and Google Forms) as solutions for administrative management. The methods applied include theoretical training, hands-on practice, and evaluation of application implementation in daily workflows. The results indicate that using Google applications accelerates data processing by up to 30%, reduces paper usage by 40%, and improves collaboration and communication effectiveness among participants. Additionally, this training fosters a transition toward a digital work culture that is adaptive and responsive to technological challenges. Thus, using Google applications has proven to be a practical and relevant solution for supporting better organizational administrative governance.